Survei Kepuasan Masyarakat terhadap Layanan Pemerintah Melalui Program MCS (Mandiri, Cerdas, dan Sehat) - Marthen Medlama; I Gusti Ayu Ngurah Kade Sukiastini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the satisfaction of the Lanny Jaya community towards the Lanny Jaya district government programs, namely the Lanny Jaya Mandiri, Lanny Jaya Smart and Lanny Jaya Sehat programs. This research method uses quantitative descriptive research by distributing questionnaires. The list of statements consists of 15 items, a questionnaire compiled using a Likert scale of 1-4 (4: Very Satisfied; 3: Satisfied; 2: Dissatisfied; 1: Very Dissatisfied). The analytical method used is Simple Statistical Analysis, namely by accumulating the number of points for each parameter that is visualized into a graph. The results of the Lanny Jaya Community Satisfaction Research on the MCS Program are that in the economic aspect, I feel satisfied, in the education aspect, I am satisfied, and in the health aspect, I am very satisfied, which can be seen from the percentage of very dissatisfied as much as 9%, dissatisfied as much as 20%, satisfied. as much as 33%, and very satisfied as much as 38%. The conclusion of this research is that the people of Lanny Jaya are satisfied and support the MCS program that has been carried out by the Lanny Jaya Regency government. Keywords: Lanny Jaya, MCS Program, Satisfaction Survey